MANAGING A PRODUCT'S MARKET POTENTIAL IN A COMPANY'S MARKETING STRATEGY (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
Marketing science is evolving rapidly, and the new economic paradigm demands proactive readiness alongside continuous monitoring of product market prospects in light of technological, market, and consumer trends. This article develops theoretical principles and applied tools for assessing product market prospects within enterprise marketing strategy, enabling informed management decisions that support business resilience.Product market prospects are defined as an integral multifactorial characteristic determining a product's potential to achieve and sustain market success in a dynamic environment. This characteristic is formed through five interrelated parameters: uniqueness, exclusivity, innovativeness, relevance of demand, and the degree to which the product meets consumers' functional, emotional, and social needs.A scoring-based toolkit is proposed, incorporating defined indices and interpretation scales to support decisions on product updates, portfolio management, and marketing strategy adjustments. Assessment is recommended periodically – every six months to one year, depending on the product, industry, and demand specifics. This enables early detection of declining market prospects as a leading signal of an approaching crisis. To ensure objectivity, assessment should involve the internal team, target audience representatives, and an external expert capable of providing independent evaluation and actionable recommendations.The article emphasizes the need to establish product market prospects management as a distinct function within enterprise marketing strategy – one that integrates innovative activity, market analytics, and consumer orientation into a unified proactive mechanism for sustaining long-term competitiveness and business resilience.
Keywords: resilience; market potential; product; marketing strategy; management; innovation